Systematic review of indoor residual spray efficacy and effectiveness against Plasmodium falciparum in Africa. Issue 1 (December 2018) - Sherrard-Smith, Ellie; Griffin, Jamie; Winskill, Peter; Corbel, Vincent; Pennetier, Cédric; Djénontin, Armel; Moore, Sarah; Richardson, Jason; Müller, Pie; Edi, Constant; Protopopoff, Natacha; Oxborough, Richard; et al.
Abstract Indoor residual spraying (IRS) is an important part of malaria control. There is a growing list of insecticide classes; pyrethroids remain the principal insecticide used in bednets but recently, novel non-pyrethroid IRS products, with contrasting impacts, have been introduced. There is an urgent need to better assess product efficacy to help decision makers choose effective and relevant tools for mosquito control. Here we use experimental hut trial data to characterise the entomological efficacy of widely-used, novel IRS insecticides. We quantify their impact against pyrethroid-resistant mosquitoes and use aPlasmodium falciparum transmission model to predict the public health impact of different IRS insecticides. We report that long-lasting IRS formulations substantially reduce malaria, though their benefit over cheaper, shorter-lived formulations depends on local factors including bednet use, seasonality, endemicity and pyrethroid resistance status of local mosquito populations. We provide a framework to help decision makers evaluate IRS product effectiveness. Indoor residual spraying is a commonly used method for mosquito, and malaria, control and there are a number of available insecticides that are available for this. Here, the authors evaluate the efficacy of widely-used and novel insecticides against pyrethroid-resistant mosquitoes.